An OOAD model of program understanding system’s parser. - Rosidi, Norazimah; Mohd Sani, Nor Fazlida; Abd Ghani, Abdul Azim (Springer Berlin Heidelberg, 2013)
This paper describes a model of parser for program understanding system. This model is developed by using Unified Modeling Language (UML). The UML is a common notation for structured modeling within Object-oriented analysis and design (OOAD) framework. It helps to specify, visualize and document models of software system. The objective of developing this model is to capture and document the details of this parser. The parser may build parse tree and abstract syntax tree (AST) which representing data structure of all elements of the source code. It also generate control flow graph (CFG) to show the flow of program. This paper describes the process of developing this model, which include creating use case diagram, class diagram, and behavior diagrams.